STUDY OF I-CONSTRUCTION IMPLEMENTATION DEVELOPMENT IN INDONESIA - Sugiarto, Amalia (Barometer, 2024)
Development will never stop, continue to grow and develop in accordance with the demands of human needs and the times. The rapid development growth in Indonesia needs to be supported by the development of innovation in the world of construction which is felt to have a far more positive impact on workers. Work in the construction sector is always limited by deadlines and costs but must produce work of good quality. One of the new innovations is the application of technology in the world of construction towards the era of the industrial revolution 4.0, namely i-Construction. I-Construction is a method that can increase productivity by utilizing IT, IoT, spatial information processing technology, robotization technology, etc. [4]. With i-Construction it can enable more readiness and efficiency thereby increasing productivity. This research was conducted using the bibliometric method in national and international journals and scientific articles, observing the construction industry in Indonesia. From the research it was found that i-Construction in the construction industry in Indonesia had only started in the last few years, which was marked by the limited application of i-Construction. The Indonesian government is also still lacking in investing in the research and development sector in terms of construction technology. These findings are expected to be the basis for initiating the application of i-Construction in the Indonesian construction industry.